POSSIBLE SOURCES OF EARTH CROSSERS - Solovaya N.A.; Pittich E.M. (My University, 2002)
We discuss the orbital evolution of solar system objects that can be sources of Earth-crossing bodies. One of the candidates of the source of Earth crossers is a group of high-inclination asteroids within the main asteroid belt. The results of their orbital evolution, obtained by numerical integration using a dynamical model of the solar system consisting of all planets, showed that, during the 200 k.y. interval that was investigated, bodies with initial inclinations within 40°-120° and eccentricities within 0.2-0.4 periodically change their inclinations, eccentricities, and perihelion distances within a rather wide range. During this time, they can reach the vicinity of the Sun and cross the Earth orbit. These bodies could potentially be dangerous for the Earth. We studied the dynamical behavior of known Solar and Heliospheric Observatory (SOHO) comets, assuming their orbits to be near parabolic. The parabolic orbits of these comets, as derived from coronographs data covering short near perihelion part of the orbits, are not precisely determined. However, it is possible to make assumptions about their near-parabolic eccentricities. Sungrazing comets discovered from the Earth with better determined orbits support these assumptions. The equations of motion of the model SOHO comets with near-parabolic eccentricities were also numerically integrated within an interval of 200 k.y.; the bodies show periodic changes in their eccentricities, inclinations, and perihelion distances. Some of these bodies come periodically to the vicinity of the Earth and can be candidates for collisions.